SOME COMMUNICATION SOLUTIONS TO PROMOTE THE DEVELOPMENT OF TOURISM TUYEN QUANG IN THE COURSE PERIOD - Nguyễn Mai, Chinh (SCIENTIFIC JOURNAL OF TAN TRAO UNIVERSITY, 2023)
In the past time, Tuyen Quang tourism has partly affirmed its position on the tourist map of the whole country, contributing to the socio-economic development of the locality. Tuyen Quang has many famous culinary specialties such as: Ham Yen crockery, San Tuyet tea, bamboo shoots, rice lam... Besides, festivals with bold identities attract many tourists such as: festivals Tuyen citadel festival, Ha temple sample procession festival, Long Tong festival... However, Tuyen Quang tourism still has many difficulties, many potentials and strengths in the province's tourism have not been invested and exploited effectively. Therefore, the synchronous implementation of solutions including communication to promote tourism development thereby promoting the local socio-economic is an important issue in the current period.